Wajda autotematyczny. Wszystko na sprzedaż i Tatarak Andrzeja Wajdy - Otto, Wojciech (Przestrzenie Teorii, 2017)
Mise-en-abîme discourse reveals itself most clearly in 2 films by Andrzej Wajda – Everything for sale and Sweet Rush. These are connected by collective reflexive contexts, as well as by a tendency to promote formal novelty. They can be analysed from the perspective of “a film in a film”, which is a story about making a film or “a film about a film”, which is a reflection on the cinematographic means of expression.